Boundary-creating processes and the social construction of threat - Tsoukala, Anastassia (2008)
Looking at the key theoretical approaches to the social construction of threat in the sociology of deviance and in political science, this article addresses the way boundaries between groups are created in different contexts. Comparison between UK media coverage of terrorists and football hooligans reveals that this is a rational process that draws boundaries on the basis of the position of the target group in the political field rather than the objective seriousness of the threat. - Reproduced.
Keywords: Terrorism